1999
DOI: 10.1515/hf.1999.033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Growth Rate and Cambial Age on Density of Rauli (Nothofagus nervosa) in Relation to Vessel Lumen Areas and Numbers

Abstract: Summary To assess the likely effects of silvicultural treatment on the wood quality of Nothofagus nervosa grown in the UK, and the possibilities of independent selection within seed origins for density and growth rate, ring width and wood density were analysed from pith to bark of 19 trees. Variations in vessel lumen size, vessel number mm−2, and total lumen area mm−2 were analysed in ten trees. Since density increased by only 0.005g cm−3 per mm increase in ring width, silvicultural practices such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 3 publications
4
13
2
Order By: Relevance
“…7). In contrast to our results, ring width in Fagus orientalis (semi-ring porous) and N. nervosa (diffuse porous) was also negatively correlated with vessel proportion and frequency, although positively correlated with mean vessel area (Denne et al 1999, Pourtahmasi et al 2011. Similarly, ring width in Q. alba (ring porous) was not correlated to the vessel proportion in earlywood (Phelps & Workman 1994).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…7). In contrast to our results, ring width in Fagus orientalis (semi-ring porous) and N. nervosa (diffuse porous) was also negatively correlated with vessel proportion and frequency, although positively correlated with mean vessel area (Denne et al 1999, Pourtahmasi et al 2011. Similarly, ring width in Q. alba (ring porous) was not correlated to the vessel proportion in earlywood (Phelps & Workman 1994).…”
Section: Discussioncontrasting
confidence: 99%
“…3a) has been also found in other oaks such as Q. suber (Leal et al 2007), Q. garrayana (Lei et al 1996), Q. macrocarpa (George et al 2002) and Q. serrata (Tsuchiya & Furukawa 2009) or in other non-related species such as Nothofagus nervosa (Denne et al 1999).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Variation in wood quality and quantity is caused by prevailing environmental conditions (e.g. Yang et al 1988;Jozsa and Brix 1989;Antonova and Stasova 1997;Dutilleul et al 1998;Lindström et al 1998;Yasue et al 2000), genetic factors (Costa e Silva 1998; King et al 1998;Denne et al 1999;Hylen 1999) and silvicultural methods (e.g. Gregg et al 1988;Denne et al 1999;Pape 1999), which affect wood formation causing changes in the number and diameter of tracheids produced by the cambium, as well as thickness and chemical composition of cell walls.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies based on xylem traits of woody species have shown that the vessel diameter has a significant positive correlation with growth rate (Denne et al, 1999;Russo et al, 2010). It has been suggested that wider vessels linked directly to higher hydraulic capacity allow faster rates of transpiration and photosynthesis, and thus increase growth rate and make tree species achieve greater heights (Brodribb and Feild, 2000;Stratton et al, 2000;Russo et al, 2010;Anfodillo et al, 2013).…”
Section: The Anatomical Patterns Of Growth Ringsmentioning
confidence: 99%